Hurry up and slow down - Marlow, Layn. (New York : Holiday House, 2009)
Hare likes to hurry through the day, unlike Tortoise, but manages to slow down for his favorite bedtime story.
2.7
K-3
Keywords: Hares -- Juvenile fiction; Turtles -- Juvenile fiction; Bedtime -- Juvenile fiction; Hares -- Fiction; Turtles -- Fiction; Bedtime -- Fiction; Rabbits -- Fiction; Turtles -- Fiction; Bedtime -- Fiction